Continuous synthesis of size-tunable silver nanoparticles by a green electrolysis method and multi-electrode design for high yield. Issue 5 (8th January 2015) - Huang, Zhihai; Jiang, Hao; Liu, Peidang; Sun, Jianfei; Guo, Dawei; Shan, Jieling; Gu, Ning
Abstract : We report the green electrochemical synthesis of size-controlled AgNPs by tuning the flow velocity in a continuous flow system, and an improved multi-electrode design for increasing the synthesis yield in unit time. Abstract : Although some methods have been developed, high-yield controllable synthesis of silver nanoparticles in aqueous solution is still challenging. Here, we report a green electrolytic synthesis of silver nanoparticles in a continuous flow system. Nanoparticle sizes could be tuned facilely by adjusting the flow velocity. Further, an improved multi-electrode electrolytic reactor was designed for increasing the yield.